Trends, Prospects and Staffing for Digital Marketing Transformation: from Internet Marketing to MarTech - I. V. Marakhina; V. A. Parkhimenko (Цифровая трансформация)
The article substantiates the importance of ensuring the eﬃciency and competitiveness of the websites of Belarusian organizations in the context of the active development of the digital economy and internetization. The study showed that Belarus is characterized not only by the quantitative growth of organizations’ websites, but also by the growth of their functionality and complexity, in which more and more processes are automated, and users perform more and more actions online. In such conditions the implementation of the possibilities of digital marketing and web analytics, as well as a new level of digital transformation of marketing such as MarTech- (MarTech) systems and solutions is critical. At the same time, the competencies of SEO specialists, who traditionally deal with the issues of website promotion on the Internet, are not enough for this. The authors propose a transition of specialists in the Republic of Belarus to a new format – specialists in digital marketing technologies and web analytics, which will be aimed at meeting the growing needs of the national economy.